Drama in education in Icelandic schools - Sonja Anna Kovacevic 1981- (2022)
This thesis focuses on drama in education and its current implementation in Icelandic compulsory schools. It traces the history of the subject and its multitude of uses. The core of the study is an email questionnaire, consisting of twelve open and closed questions regarding the implementation of drama in Icelandic schools, that has been sent to a sample of 119 schools. To cover the whole of Iceland attention was paid to sending the questionnaire to at least one compulsory school of each Icelandic Local Authority (sveitarfélag), with special emphasis on the Greater Reykjavík area (höfuðborgarsvæðið), as this area has the highest population density. The survey received a response rate of around 70%. By comparing the research to other research in the field from the last 13 years, a trajectory for drama in education in Iceland was distinguished. The survey revealed that today, the importance of drama in education is widely known among school principals and teachers, and the number of schools that teach drama seems to have increased since drama became a compulsory subject on the curriculum. But still not all schools teach the subject. The circumstances of how drama is being taught and by whom remain largely unchanged when compared to previous studies. In the majority of schools, the subject is not taught by teachers who are educated to teach drama. Drama is often taught in the form of short-term courses (lota in Icelandic) or in elective courses. It is also common that drama is only taught at special times in the school year, such as to prepare for annual festivals or Christmas festivities. Through comparing the study to previous studies in the field, possible reasons why the circumstances of drama education in Iceland remain largely unchanged are uncovered, and how to strengthen drama education in Icelandic schools. Ritgerðin fjallar um leiklistarkennslu í grunnskólanámi og framkvæmd hennar í íslenskum grunnskólum í dag. Saga viðfangsefnisins er fyrst rakin sem og margvísleg notkun leiklistar í menntun en ...